The Evolution of Secularism in Kazakhstan: Legal Frameworks and Official Discourses - Makpal Davletyarova (Fenomena, 2025)
This article examines the evolution of secularism in Kazakhstan from 1991 to 2023. The Constitution of the Republic affirms secularism by guaranteeing neutrality and freedom of conscience, yet the state actively endorses Sunni Islam of the Hanafi school and Russian Orthodoxy. Previous research on Kazakhstan has primarily focused on state control of religion and the securitization of Islam, while the legal framework and political discourse remain underexplored. This study addresses this gap by analyzing the implementation of secularism in public rhetoric and legal documents over time. In addition, it relies on a qualitative analysis of the Constitutions, relevant laws, and key statements by national leaders. The study reveals that secularism in Kazakhstan has evolved. It has shifted from a neutral approach in the 1990s to an ideological framework that primarily associates secularism with state-approved religions. In this context, the authorities support certain denominations while displacing alternative faiths. Thus, Kazakhstan’s approach to secularism maintains the official separation of religion and state while supporting religious groups that align with state-approved beliefs and values. Artikel ini mengkaji evolusi sekularisme di Kazakhstan dari tahun 1991 hingga 2023. Konstitusi Republik Kazakhstan menegaskan prinsip sekularisme dengan menetapkan netralitas dan kebebasan berkeyakinan, namun negara secara aktif mendukung Islam Sunni mazhab Hanafi dan Ortodoksi Rusia. Penelitian sebelumnya tentang Kazakhstan umumnya berfokus pada isu-isu seperti kontrol negara terhadap agama dan pengamanan terhadap Islam, namun jarang menelaah kerangka hukum dan wacana politik. Studi ini mengisi kesenjangan tersebut dengan menganalisis penerapan sekularisme dalam retorika publik dan dokumen hukum dari waktu ke waktu. Selain itu, penelitian ini menggunakan analisis kualitatif terhadap Konstitusi, undang-undang, dan pernyataan penting dari para pemimpin nasional. Hasil penelitian menunjukkan bahwa sekularisme di Kazakhstan telah berkembang: dari pendekatan netral pada tahun 1990-an menjadi kerangka ideologis yang terutama mengaitkan sekularisme dengan agama-agama yang disetujui negara. Dalam konteks ini, otoritas negara mendukung denominasi keagamaan tertentu sambil mengesampingkan kepercayaan alternatif. Dengan demikian, pendekatan terhadap sekularisme di Kazakhstan mempertahankan pemisahan resmi antara agama dan negara, namun memberikan dukungan kepada kelompok agama yang sejalan dengan nilai-nilai dan keyakinan yang disetujui negara.